Método para investigação do comportamento empreendedor - Santos, Michelle Steiner dos (2004)
The main goal of this work is the elaboration and application of an appropriate method to analyze behavior aspects, necessities, typology (attitude and dominant function) of entrepreneurs and non-entrepreneurs; to proceed with a bibliography revision about development concepts, maturation, learning and personality; and verify the influence of vocational aspects on the structuring of the of the entrepreneur behavior. This study is essentially an investigative and qualitative research, which came out of the following problem: “how to investigate the motivating and learning factors that characterize the entrepreneurs and non-entrepreneurs behavior”? With the purpose to access the performance of the proposed method (inventory, genogram of the careers and interview), the history of the lives of eleven subjects (persons) from the Northeast and the South regions of Brazil have been analyzed (study of cases) during the period from March of 2003 to March of 2004. The conclusion taken from the research is that the method is effective, ant also that several positive factors (personal, environmental and aleatory) have their influence to shape the profile of the behavior of the entrepreneur. Within that context the capacity to act in an enterprise can be influenced by the quantity and the quality of input and experiences lived by the human being mainly during the childhood and youthfulness (within the relative, social and cultural relations), and by historic aspects, economic and geopolitical situation of the country and of the world.